THE DEVELOPMENT OF PheT-BASED STUDENT WORKSHEETS TO IMPROVE STUDENTS’ COGNITIVE LEARNING OUTCOMES AT MTS NUR HADI MUARA JAWA - M. Sholeh (JEE (Journal of English Education), 2025)
This study aims to develop PhET-based student worksheets (LKPD) and examine their effectiveness in improving students’ cognitive learning outcomes at MTs Nur Hadi Muara Jawa. The research employed a research and development (R&D) design using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects of the study were MTs students selected through purposive sampling. Data were collected using expert validation sheets, student response questionnaires, and cognitive achievement tests administered before and after the implementation of the worksheets. The data were analyzed using descriptive statistics and inferential analysis to measure learning gains. The findings indicate that the PhET-based LKPD are valid, practical, and effective in enhancing students’ cognitive performance, particularly in understanding abstract scientific concepts. The integration of interactive simulations encourages active learning, inquiry processes, and conceptual understanding. Therefore, PhET-based student worksheets can serve as an effective instructional material to support digital-based science learning in secondary education.